(untitled) (Journal of Computational Mathematics, 2000)
Some Jacobi approximations are investigated, which are used for numerical solutions of differential equations on the half line. The stability and convergence of the proposed schemes are proved. The main idea and techniques in this paper are also applicable to other problems on unbounded domains.